Digital Promotional Strategies Broaden Brand Awareness For Industrial Tool Providers: Strategi Promosi Digital Memperluas Kesadaran Merek Untuk Penyedia Alat Industri - Niken Amelia Putri; Alshaf Pebrianggara (Procedia of Social Sciences and Humanities, 2026)
General Background The Industry 4.0 era integrates cyber technology into commercial operations, necessitating modern online methods to maintain market competitiveness. Specific Background Conventional sales approaches, such as physical banners and direct corporate visits, restrict the market visibility of traditional steel and tool suppliers among individual retail buyers. Knowledge Gap Many traditional industrial businesses lack the necessary technological adaptation and digital market mapping required to transition from offline operations to reach wider retail audiences. Aims This descriptive qualitative research formulates and applies data-driven online frameworks to widen the audience reach and market recognition of a conventional technical equipment enterprise. Results Demographic data analysis and search trend evaluations guided the establishment of an optimized e-commerce storefront and a search engine business profile. Platform performance metrics revealed that targeted online advertisements and comprehensive digital profiles successfully generated verifiable audience interactions and widened search visibility specifically among male consumers over twenty-five years old. Novelty The study demonstrates a practical transition model for traditional equipment suppliers, utilizing search trend analytics to select optimal e-commerce platforms and commercial naming conventions. Implications Adopting these targeted online frameworks allows conventional industrial suppliers to significantly widen their market exposure and establish fundamental consumer trust, creating a necessary foundation for future retail transactions. Highlights:  Demographic data evaluated optimal electronic commerce platforms capturing male buyers over twenty-five. Search trend analytics directed storefront naming conventions maximizing online visibility. Business profiles and targeted advertisements generated measurable audience interactions and widened market access. Keywords: Search Engine Optimization, Electronic Commerce Platforms, Market Visibility, Consumer Demographics, Business Profiles